An Analysis of Figurative Language and Meaning in “Drive You Home” Song Lyrics by Jackson Wang - Sa-ae, Sureena; Ira Maisarah (UNIB Press, 2024)
Figurative language is language that uses figures of speech rather than literal meaning and is frequently used in literature to give vitality and interest to the author’s writing. The purpose of this study is to identify the type of figurative language used in the lyric ‘Drive You Home’ and to analyze the connotative and contextual meaning of figurative language in that song lyric. The descriptive qualitative method is used in this study. The result of this study found that there is some figurative language used in Jackson Wang’s song entitled ‘Drive You Home’, such as simile, metaphor, allegory, hyperbole, and symbol. The connotative and contextual meaning of each figurative language is also clarified.